Comparative Analysis of Sensitivity of Canine and Human Erythrocytes to Changes in Osmotic Conditions of the Medium - Hubenia, Yevhenii; Yershov, Serhii; Chabanenko, Olena; Shpakova, Nataliia (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(4):289